Pelatihan pembuatan pestisida nabati menggunakan buah maja pada kelompok tani Desa Bontotiro di Kabupaten Bantaeng - Nur Anny S. Taufieq; Raeni Tenriola; Dwi Wahyuni Aprianti (Universitas Negeri Makassar, 2019)
The Community Partnership Program (PKM) partner is the Bontotiro Village Farmer Group of Bantaeng Regency. The problem is the lack of knowledge of the farming community about the use of maja fruits as ingredients for vegetable pesticides. Therefore, farmers need to be equipped with knowledge of how to make vegetable pesticides by using maja fruits. The methods that will be used are mentoring and participatory rural approach (PRA) methods. Assistance methods are used to increase the understanding of the farming community regarding the use of maja fruits as ingredients for vegetable pesticides and to facilitate partners in making vegetable pesticides. The PRA method is carried out to arouse the partner's sense of belonging to the product to be developed, and the partner's sense of responsibility towards the product and the environment around it. The main methods adopted in the Community Partnership Program (PKM) activities are lectures, discussions, questions and answers, and simulations. The results achieved are the maja fruit, which has only been used as household appliances because it has a hard shell. At present, the maja flesh can already be used as a vegetable pesticide, which has high economic value. Making vegetable pesticides using maja flesh is very beneficial for the needs of farmers because it can reduce the use of chemical fertilizers that have an impact on damage to environmental functions and natural resources.